Ocular findings in neurosyphilis: a retrospective study from 2012 to 2022 - Huanhuan Cheng; Haocheng Zhu; Gang Shen; Yaqi Cheng; Jiao Gong; Juan Deng (Frontiers in Neurology)
PurposeThis study aimed to investigate ocular manifestations in patients with neurosyphilis and their association with general indexes.MethodsThis retrospective study was conducted among patients who were hospitalized for neurosyphilis from 2012 to 2022. Clinical manifestations, laboratory tests, brain MRI, and ocular examinations were reviewed and analyzed.ResultsA total of 106 neurosyphilis patients were included, of which 10 patients presented with ocular signs as their initial symptoms. The most common main complaint was reduced vision (6/10), followed by diplopia (2/10) and ptosis (2/10). The causes of vision loss included optic neuropathy (4/6) and posterior uveitis (2/6), with all six patients showing optic nerve involvement. A total of 29 (27.4%) patients exhibited pupil abnormalities. A lumbar puncture was performed on all 106 patients, and abnormal cerebrospinal fluid (CSF) findings were revealed in 101 (95.3%) patients, indicating central nervous involvement. The median white blood cell count in the CSF of the patients with pupil abnormalities was significantly higher than that of those without pupil abnormalities (14.0 vs. 6.0 cells/μl, p = 0.037). In addition, the patients with abnormal pupillary light reflex (PLR) were more likely to have multiple brain lesions compared to those with normal PLR (77.3% vs. 29.2%, p < 0.001).ConclusionOptic nerve involvement is the main cause of vision loss in neurosyphilis. Patients with optic neuropathy or posterior uveitis should undergo prompt diagnostic evaluation for syphilis. Pupil abnormalities can serve as indicators of more severe CSF and MRI findings.